1978
DOI: 10.1258/002367778780953080
|View full text |Cite
|
Sign up to set email alerts
|

Cannibalistic traits observed in rats treated with a teratogen

Abstract: 81 SummaryRat offspring malformed as a result of maternal exposure to a teratogen were cannibalized preferentially to apparently normal offspring. Lack of viability also appeared to be a factor in the cannibalistic tendency, since both normal and malformed dead pups were consumed more frequently than viable pups of either category. Of the 29 cannibalized pups observed, 86 % were cannibalized in the 1st 24 h.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…Furthermore, females who give birth to deformed offspring were found more likely to consume their deformed offspring or dead young than their living healthy siblings [40], [41]. Schardein et al ., [41] reported that 21% of live congenitally malformed offspring were killed and consumed in contrast to only 3% of normal live offspring. Similarly among stillborn offspring, the females consumed 63% of the congenitally malformed ones but only 19% of the normal ones [41].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, females who give birth to deformed offspring were found more likely to consume their deformed offspring or dead young than their living healthy siblings [40], [41]. Schardein et al ., [41] reported that 21% of live congenitally malformed offspring were killed and consumed in contrast to only 3% of normal live offspring. Similarly among stillborn offspring, the females consumed 63% of the congenitally malformed ones but only 19% of the normal ones [41].…”
Section: Discussionmentioning
confidence: 99%
“…Strain and hormonal differences have been shown to influence pup-killing behaviour by female mice [38], [39]. Furthermore, females who give birth to deformed offspring were found more likely to consume their deformed offspring or dead young than their living healthy siblings [40], [41]. Schardein et al ., [41] reported that 21% of live congenitally malformed offspring were killed and consumed in contrast to only 3% of normal live offspring.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The litter size, however, was within the reference range given by the Møllegaard breeding centre (average number of total offspring: 9–11). It is known that malformed or non‐viable pups, induced by teratogen treatment of the rat mother, are cannibalized shortly after birth (Schardein et al ., 1978). Gross abnormalities were not detected among our surviving DES pups, but might still have been present in those which were subject to infanticide.…”
Section: Discussionmentioning
confidence: 95%
“…Exposure of laboratory rats to environmental stresses, including teratogen (6-aminonicotinamide) and aflatoxin was found to increase cannibalism in these animals (Schardein et al, 1978;Shankarmurti et al, 1972). Exposure of laboratory rats to environmental stresses, including teratogen (6-aminonicotinamide) and aflatoxin was found to increase cannibalism in these animals (Schardein et al, 1978;Shankarmurti et al, 1972).…”
Section: Environmental Aspects Of Zoonotic Diseasesmentioning
confidence: 99%